An analysis of the Medicago falcata s.l. alfalfas collected in the ex-USSR territories for the fullness of their coverage - N. Yu. Malysheva; L. L. Malyshev (Труды по прикладной ботанике, генетике и селекции)
Background. The collection of wild yellow alfalfas from the Medicago falcata s.l. complex maintained at the N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) is a unique genetic stock collected while exploring the ex-USSR territories from 1924 to 2018. It includes Medicago falcata L. proper, M. borealis Grossh., M. romanica Prod., M. quasifalcata Sinsk., M. difalcata Sinsk., and M. glandulosa David. Gap analysis makes it possible to assess the sufficiency of VIR’s collecting efforts in a certain locality or administrative unit and plan further collecting activities to ensure comprehensive conservation of sickle alfalfa genetic diversity.Material and methods. Databases of the Perennial Forage Crop Genetic Resources Department at VIR, and digital maps of administrative subdivisions of Russia and neighboring countries served as the research material. The ex-USSR administrative subdivisions were accepted as operational units. For each of them, the number of ser. Falcatae Vass. species and the number of accessions per administrative subdivision were taken into account. Statistical data processing included construction of frequency tables and differentiated mapping.Results. The coordinates of collection sites were identified for 446 accessions. Collections of six wild species within the studied complex were analyzed across the ex-USSR space, and in more detail in Krasnodar Territory.Conclusion. The target areas were identified for further collecting activities. For Russia, the prioritized regions where the collection could be replenished are the northern frontier of the area of sickle alfalfa distribution in the European part and its eastern borderline in Siberia, both characterized by extreme environmental conditions. To increase the geographic diversity of the collection, additional collecting efforts are required, along with mobilization of accessions from the neighboring countries.